Vibration transmissibility of low frequency isolator - Le , Thanh Danh; Nguyen , Vu Anh Duy (Journal of Technical Education Science, 2021)
It is known that the quality of a vibration isolation system can be improved by reducing the stiffness of the system. However, in this way, the load supporting capacity of isolator cannot be maintained. In order to eliminate the dichotomy between the load bearing capacity and the reduction in stiffness, this paper will introduce a low frequency vibration isolator. First, the relationship between the configurative parameters and the dynamic stiffness of the isolator is obtained. Then, the characteristic of the motion transmissibility of the system at the steady state is analyzed through the normal form solution (NH). From this analysis result, the curve of the vibration transmission is predicted. The simulation results confirm that the isolation effectiveness of this model is better than that of the traditional model when the dimensionless dynamic stiffness at the equilibrium position is lower than one and bigger than zero or equal to zero. Besides, these results furnish a useful insight for the design of the low frequency vibration isolation model.